The association of molecular classification with fertility-sparing treatment of atypical endometrial hyperplasia and endometrial cancer: a retrospective study - Wang, Yuanyuan; Lai, Tianjiao; Chu, Danxia; Bai, Jing; Yan, Shuping; Guo, Ruixia (Frontiers in Oncology, 2025)
BackgroundTo evaluate whether molecular classification was associated with treatment response and recurrence in women with atypical endometrial hyperplasia (AEH) or early-stage endometrial cancer (EC) treated with progestin.MethodsA retrospective analysis of 116 patients (71 AEH and 45 EC) who received fertility-sparing therapy between 2010 and 2022 was performed. Tumors were classified via immunohistochemistry and gene sequencing into four subgroups: polymerase-ϵ (POLE)-mutated (POLEmut), tumor protein 53 (p53) wild type [p53wt; no specific molecular profile (NSMP)], mismatch repair deficient (MMRd), and p53 abnormal (p53abn). The primary outcome was complete response (CR) to hormone therapy. The secondary outcomes included the recurrence rate after CR and conception success. The treatment response to progestin and recurrence rate were compared across the four subgroups.ResultsOf 116 patients, 10 (8.62%) were classified as POLEmut, 81 (69.82%) p53wt, 9 (7.76%) p53abn, and 16 (13.76%) MMRd. At the 12-month evaluation, 87 patients (75.00%) achieved CR (median treatment duration, 5.95 months; range, 1.6–12.9). Partial response (PR), stable disease (SD), and progressive disease (PD) rates were 6.89% (n = 8), 1.72% (n = 2), and 16.38% (n = 19), respectively. Patients with the p53abn and MMRd subtypes had lower CR rates (33.33% and 37.50%) and higher progression rates (44.40% and 37.50%) compared to other subgroups (p < 0.05). After 24-month follow-up, recurrence rates were markedly higher in the p53abn (100%) and MMRd (83.33%) subgroups versus the POLEmut (33.33%) and p53wt (17.39%) subgroups (p < 0.05). Among 56 (64.37%) patients attempting conception, the pregnancy rate of 38 patients who received in vitro fertilization-embryo transfer was 47.37% (18/38), and the pregnancy rate of 18 patients who chose natural pregnancy was 16.67% (3/18), showing no statistical difference (p = 0.072).ConclusionMolecular classification may be associated with hormone treatment response in patients with AEH, EC patients with POLEmut and p53wt had better progestin response, and those with MMRd and p53abn had the poorest response and the highest recurrence rate. Recurrence was common after CR, but close review is necessary. For further investigation of the role of molecular classification in fertility-sparing treatment of AEH/EC, larger prospective studies are necessary.